Phased-MIMO Radar for Automotive Application - muttaqin hardiwansyah (Universitas Trunojoyo Madura, 2022)
Nowadays, radar is not only used to detect aircraft, but has been used to detect other objects such as birds, motor vehicles and others. Vehicle radar is currently one of the interesting fields to be developed. Multiple input Multiple Output (MIMO) radar systems have been widely used, with the advantages of increasing the number of targets that can be detected, wider detection angles, etc. The disadvantages of MIMO systems in radar include high gain, increasing the resolution of the object detection angle, being able to distinguish small and large objects due to differences in the radar cross section of reflected objects, etc. called phased array systems. Phased-MIMO combines the advantages of MIMO and phased-array, where PMIMO radar has diversity as well as coherent gain. PMIMO radar is an array of antenna arrays grouped into several sub-arrays that are in phase as in phased-array and between sub-arrays emit orthogonal signals. The use of PMIMO in vehicle radar in this study aims to increase the number of detected targets and be able to distinguish between small objects and large objects, for example PMIMO radar can distinguish between motorbikes, cars and trucks so that the vehicle is able to make the right decision. Whether the vehicle will brake, overtake or just shift slightly to avoid the motorcycle.